SIMALUNGUN BATAK CULTURE LEARNING BASED ON MULTIMEDIA APPLICATIONS USING THE COMPUTER ASSISTED INSTRUCTION (CAI) METHOD - Pandi barita nauli Simangunsong; Syarifah Fadillah Rezky; Dewi wahyuni (LPPM Politeknik LP3I Medan, 2020)
Simalungun Batak culture is a custom inherited from previous generations that still exists today. Still, the influence of the development of the current era is the lack of community knowledge of Simalungun Batak cultures such as Batak scripts, Batak traditional houses, musical instruments, and others, this due to the lack of education given to the community especially to school children so that the knowledge of the Simalungun Batak culture becomes less. The introduction of Simalungun Batak culture is applied with a multimedia-based learning model to be more practical and more comfortable to understand, where this learning uses multimedia-based instruction that is on the computer that is said to be Computer-assisted Instruction. The development of schoolchildren's understanding of the teaching of the Simalungun Batak culture has become faster. This is helped by multimedia-based learning that uses instructions from the computer.